2011
DOI: 10.1177/0009922810390512
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Features of Children Hospitalized With Pandemic 2009 A:H1N1 and Seasonal Influenza

Abstract: There was no significant difference between the groups in measures of severity during hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
3
17
0
1
Order By: Relevance
“…Despite the high proportion of children with an underlying chronic medical condition, only 3% of children were admitted to the ICU, which is quite below a higher rate of 20–26% reported in other studies [16,17]. This low percentage might reflect the milder form of the infection among children in Kuwait and that half of the admitted children had previously been healthy.…”
Section: Discussionmentioning
confidence: 70%
“…Despite the high proportion of children with an underlying chronic medical condition, only 3% of children were admitted to the ICU, which is quite below a higher rate of 20–26% reported in other studies [16,17]. This low percentage might reflect the milder form of the infection among children in Kuwait and that half of the admitted children had previously been healthy.…”
Section: Discussionmentioning
confidence: 70%
“…This is in contrast with most previous studies which reported higher rates of asthma in children with pH1N1 children, with percentages up to 50%. 3,4 However, in a study in Argentina, only 6% of children hospitalised with pH1N1 had a history of asthma. 11 Four of seven children in the ICU had an underlying illness and three of them a neurological disorder, which has been shown to be an important risk factor for admission to an ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Several paediatric studies 1-5 comparing pH1N1 with seasonal influenza had demonstrated greater morbidity and mortality with pH1N1 4,5 while others had revealed a mild course comparable with seasonal influenza. [1][2][3] Nowadays, pH1N1 is considered to be a seasonal influenza subtype. However, in clinical and epidemiological practice it is helpful to understand the differences between these two types.…”
Section: Introductionmentioning
confidence: 99%
“…This high number of cases reported in the ongoing ESPED study may be partly due to an increased awareness in physicians regarding the new subtype of influenza with unclear severity at the start of the pandemic, resulting in more frequent laboratory testing and diagnosis of influenza [5,24]. Additionally, the higher number of PICU admissions may be due to a truly higher severity of the pandemic influenza A (H1N1) 2009 subtype in children compared to previous seasonal influenza subtypes [e.g., [18,25]], although not all studies report such a difference in severity [26,27], or found a difference only regarding risk groups [28]. Thus, a comparison of both ESPED studies on the absolute number of severe influenza cases [24] has to be regarded with caution, and may underestimate the importance of severe seasonal influenza caused by non-pandemic influenza virus subtypes in children in Germany.…”
Section: Discussionmentioning
confidence: 99%